Gambaran Kelengkapan Informasi Medis Dan Keakuratan Kode Diagnosis Di Rumah Sakit Bhayangkara Bengkulu - Harmanto, Deno; Budiarti, Anggia; Herisandi, Ari (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2022)
Medical records must contain medical data that describes in detail all aspects of patient care that occur. Hospital Minimum Service Standard Completeness of medical record filling 24 hours after completion of service is 100%. Incomplete medical record filling describes the health services provided and the quality of medical record services. Incomplete medical record documents will make it difficult for officers to recognize the patient's medical history and claims to insurance companies. The aim is to find out the description of the completeness of inpatient medical information on the accuracy of the ICD-10 based diagnosis code at Bhayangkara Hospital Bengkulu. The research method used was descriptive research, namely collecting data by direct observation of the research object. The sample in this study consisted of 83 inpatient medical record files. Results: Of the 83 inpatient medical record files, 42 sheets were filled out in the Anamnesa sheet with the percentage (51%) not filled in completely, laboratory examination results totaling 36 sheets with the percentage (44%) not filled out completely, the medication record sheet was more than partial totaling 46 sheets with a percentage (55%) not filled in completely, and writing patient diagnoses, namely more than a portion of 49 sheets with an unclear percentage (59%).